2009
DOI: 10.1055/s-0029-1216880
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Olefination Reactions Promoted by Rieke Manganese

Abstract: A study of the advantages of using manganese, an inexpensive and nontoxic metal, to perform stereoselective b-elimination reactions and to promote sequential olefination reactions of aldehydes to obtain a,b-unsaturated esters and amides is presented. Various elimination reactions, all of them characterized by occurring with complete stereoselectivity and in high yields, were performed using active manganese (Mn*) as metalating agent. This ability of manganese has been applied to develop a novel and direct synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…[12] Morpholine amides are a safe alternative [13] to Weinreb amides but have similar modes of reactivity and comparable ease of manipulation. [14] We quickly found that excellent results were obtained when the hydroboration of 8 with ( l Ipc) 2 BH[15] was performed in Et 2 O at 0 °C for 2 h, followed by addition of 0.85 equiv of aldehyde at −78 °C (Scheme 2). By using this procedure, the syn -α-methyl-β-hydroxy morpholine amides 11a–f were obtained in good to excellent yields (68–91%) and with excellent enantio- and diastereoselectivities (96–98% ee, d.r.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[12] Morpholine amides are a safe alternative [13] to Weinreb amides but have similar modes of reactivity and comparable ease of manipulation. [14] We quickly found that excellent results were obtained when the hydroboration of 8 with ( l Ipc) 2 BH[15] was performed in Et 2 O at 0 °C for 2 h, followed by addition of 0.85 equiv of aldehyde at −78 °C (Scheme 2). By using this procedure, the syn -α-methyl-β-hydroxy morpholine amides 11a–f were obtained in good to excellent yields (68–91%) and with excellent enantio- and diastereoselectivities (96–98% ee, d.r.…”
mentioning
confidence: 99%
“…[1–7,23] The morpholine amide unit in the aldol products exhibits Weinreb amide-like ease of manipulation in subsequent steps. [13,14] Our procedure requires only two steps, starting with the straightforward synthesis of diisopinocampheylborane. [15] Strikingly, the cost of raw materials required for the synthesis of enolborinate 9 Z (including the synthesis of diisopinocampheylborane) is less than $0.25 per mmol scale aldol reaction (2012 Sigma-Aldrich prices for bulk quantities of reagents).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction was also Z-selective but yields with the substrates tested were lower (62-64%). 146 In order to replace Cr II with a less expensive and less toxic metal, Falck studied the reaction of ethyl dichlorofluoroacetate with benzaldehyde using Fe. Thought the yield was lower (79%) than with the Cr II version (99%), the reaction was still Z-selective.…”
Section: Trisubstituted Monofluoroalkenesmentioning
confidence: 99%
“…Dichlorides -important class of intermediates in organic synthesis. They were used for alkenylation of carbonyl compounds [15,16], cyclopropanation and epoxidation [17][18][19], dimerization [20,21] and others [22][23][24][25]. In addition, geminal dichlorides are encountered as structural motifs in polyhalogenated natural products [26,27] (Fig.…”
Section: Introductionmentioning
confidence: 99%